Influence of deposited CNTs on the surface of carbon fiber by ultrasonically assisted electrophoretic deposition. Issue 1 (June 2015) - Jiang, J J; Liu, F; Deng, C; Fang, L C; Li, D J
Abstract: The surface property of carbon fiber directly affects the interface performance between carbon fiber and matrix. To improve the surface property of carbon fiber, we proposed a simple method to prepare carbon nanotubes /carbon fiber hybrid fiber via ultrasonically assisted electrophoretic deposition (EPD). Surface morphologies and surface functional group of carbon fibers were examined by atomic force microscopy (AFM), scanning electron microscopy (SEM) and fourier transform infrared spectrometer (FTIR), respectively. The results show that the deposition of carbon nanotubes changed the surface morphologies of carbon fibers and introduced polar groups (C=O and C-O) to carbon fiber surface. Comparing the results with EPD-only, ultrasonically assisted EPD increased the uniformity of carbon nanotubes coatings whereas only sparse and not uniformly deposition formed without ultrasonic.